From one-pot stabilisation to in situ functionalisation in nitroxide mediated polymerisation: An efficient extension towards atom transfer radical polymerisation - Petton, Lionel (2012)
A one-pot controlled method for the nitroxide end-group removal from synthetic polymers prepared by nitroxide mediated polymerisation (NMP) is reported. The strategy relies on the controlled addition of compounds such as thiols, radical initiators and carbon tetrabromide with high chain transfer constants. From a practical point of view, when the desired molar mass and conversion are reached, 1 to 10 equivalents of the transfer agent compared to the nitroxide are added and a few minutes later, after transformation of all chain-ends, the reaction is quenched. The versatility of the procedure was successfully tested with a wide range of monomers (styrene (S), isobornyl acrylate (iBA) or methyl methacrylate (MMA)) and nitroxides (2,2,6,6- tetramethyl-1-piperidinyloxy (TEMPO) and N-tert-butyl-1-diethylphosphono-2,2- dimethylpropyl nitroxide (SG1)). The removal of the nitroxide end-group proceeds with high fidelity for all the transfer agents studied, while at the same time the thermal stability of the resulting polymer chains increases when thiols are employed. Furthermore, a functional group that allows for chain extension by atom transfer radical polymerisation (ATRP) has been introduced through the direct synthesis of bromine terminated macroinitiators via a chain transfer reaction with carbon tetrabromide.